Ownership and Utilisation of Long-Lasting Insecticidal Nets in Tiko Health District, Southwest Region, Cameroon: A Cross-Sectional Study - Paulette Ngum Fru; Frederick Nchang Cho; Andrew N. Tassang; Celestina Neh Fru; Peter Nde Fon; Albert Same Ekobo (Journal of Parasitology Research)
Introduction. Malaria is and remains a serious health concern in Africa. In Cameroon, where malaria is endemic and a major public health problem, the major control measure put in place is the use of long-lasting insecticidal nets (LLINs). In the Tiko Health District (THD), the challenges have been to assess and to evaluate the ownership and utilisation of LLINs. This study sought to assess the ownership and utilisation rates of LLINs in the THD. Methodology. A cross-sectional survey involving 418 households was conducted in four health areas in the THD. A structured questionnaire was used to collect data on LLIN ownership and utilisation as well as sociodemographic characteristics. Results. The ownership of at least one LLIN per household, coverage, and accessibility were, respectively, 89%, 56.2%, and 66.3%, while installing LLINs on all beds in the household, sleeping under LLINs the previous night (SULPN), and universal utilisation were 72%, 24.9%, and 14.1%, respectively. Factors significantly associated with the ownership of at least one LLIN per household were respondent’s age and gender. Heat (21.1%) and forgetfulness (6.5%) were the main reasons postulated for irregular utilisation of LLINs. Conclusion. The ownership LLINs failed to guarantee utilisation and definitely effective control of malaria in the THD, as expected. Continuous and appropriate use of LLINs is indispensable, in addition to periodic sanitation, booster campaigns of LLIN distribution, and evaluation research for effective prevention and control of malaria.